PRUNE-BELLY SYNDROME-ASSOCIATED WITH OMPHALOCELE IN A FEMALE NEWBORN - GUVENC, M; GUVENC, H; AYGUN, AD; YALCIN, O; BAYDINC, YC; SOYLU, F (W B Saunders Co, 1995)
The authors report on a female newborn with prune-belly syndrome (PBS) in association with omphalocele. This case raises the total of omphalocele associated with PBS to seven. The authors suggest that this case lends support to the concept of PBS being caused by an early disturbance of mesodermal development in both the abdominal wall and the urinary tract. Copyright (C) 1995 by W.B. Saunders Company
Keywords: PRUNE-BELLY SYNDROME; FEMALE; OMPHALOCELE